Substrate combinations in potato planting to increase the production of minitubers - Corso, Talita Gomes; Ferraz-Almeida, Risely (Comunicata Scientiae, 2024)
The profitability and initial development of potatoes depend on the type of substrate used in planting. Therefore, this study aimed to evaluate combinations of substrates for the production of minitubers of potatoes. An experiment was carried out with the combinations of substrates based on sphagnum peat, coconut fiber, rice husks, and expanded vermiculite [TFCV]; and sphagnum peat and expanded vermiculite [TV], in different proportions (100%; 75%; 50%; 25%), with five replications. The treatments were: (i) TFCV100%; (ii) TFCV75%+TV25%; (iii) TFCV50%+TV50%; (iv) TFCV25%+TV75%; and (v) TV100%. At 40 and 70 days after planting (DAP), the development of shoots, tubers, and roots was monitored. Results showed that the isolated application of TV showed the highest production of fresh mass of tubers (93.0 g), and fresh (0.28 g) and dry mass of roots (0.17 g). At 40 DAP, tuber production was highly correlated with the root part (r: 0.77). However, after 70 DAP, tuber production was associated with shoot development (r: 0.66). If is necessary to mix substrates recommend the mixing of TFCV50% + TV50%. The addition of coconut fiber and rice husk increases the availability of nutrients in the substrate with a positive effect on the aerial development of the plants.